Enterprising veterinarians: engagers of the "One Health" approach to overcome zoonotic diseases - Imad Ibrahim Ali Al-Sultan (Vet Pulse, 2010)
The Faculty of Veterinary Medicine (FPV) at Universiti Malaysia Kelantan (UMK) was established in 2009. Since then, pioneering staff and students have been actively challenged to realise the University's vision of churning out enterprising graduates. Stimulated by this vision, the faculty continuously provide experential learning opportunities to students so that when they graduatethey are more sought after because of their enterprising nature.